Chlorine disinfection increases both intracellular and extracellular antibiotic resistance genes in a full-scale wastewater treatment plant. (1st June 2018) - Liu, Shan-Shan; Qu, Hong-Mei; Yang, Dong; Hu, Hui; Liu, Wei-Li; Qiu, Zhi-Gang; Hou, Ai-Ming; Guo, Jianhua; Li, Jun-Wen; Shen, Zhi-Qiang; Jin, Min
Abstract: The emergence and spread of antibiotic resistance has posed a major threat to both human health and environmental ecosystem. Although the disinfection has been proved to be efficient to control the occurrence of pathogens, little effort is dedicated to revealing potential impacts of disinfection on transmission of antibiotic resistance genes (ARGs), particularly for free-living ARGs in final disinfected effluent of urban wastewater treatment plants (UWWTP). Here, we investigated the effects of chlorine disinfection on the occurrence and concentration of both extracellular ARGs (eARGs) and intracellular ARGs (iARGs) in a full-scale UWWTP over a year. We reported that the concentrations of both eARGs and iARGs would be increased by the disinfection with chlorine dioxide (ClO2 ). Specifically, chlorination preferentially increased the abundances of eARGs against macrolide ( ermB ), tetracycline ( tetA, tetB and tetC ), sulfonamide ( sul1, sul2 and sul3 ), β -lactam ( ampC ), aminoglycosides ( aph(2')-Id ), rifampicin ( katG ) and vancomycin ( vanA ) up to 3.8 folds. Similarly, the abundances of iARGs were also increased up to 7.8 folds after chlorination. In terms of correlation analyses, the abundance of Escherichia coli before chlorination showed a strong positive correlation with the total eARG concentration, while lower temperature and higher ammonium concentration were assumed to be associated with the concentration of iARGs. This study suggests the chlorine disinfection could increase the abundances of both iARGs and eARGs, thereby posing risk of the dissemination of antibiotic resistance in environments. Graphical abstract: Highlights: Impact of chlorination on eARGs pollution in UWWTPs were for the first time reported. Chlorination disinfection enhanced both eARGs and iARGs pollution. Extracellular tetM and sul1 were the most dominant eARGs in the final effluent. E. coli showed a positive correlation with the total eARG concentration after chlorination.